Roles played by IL-8 in altering dynamics of trabecular meshwork cells after human cytomegalovirus infection - Ehara, Fumie; Nagase, Daisuke; Kai, Masachika; Adachi, Kaori; Miyake, Hitomi; Shimizu, Yumiko; Inoue, Yoshitsugu; Miyazaki, Dai (Frontiers in Cellular and Infection Microbiology, 2025)
Open-angle glaucoma (OAG) is the leading cause of blindness worldwide. Human cytomegalovirus (HCMV) is known to infect the trabecular meshwork cells (HTMCs) and corneal endothelial cells leading to chronic and recurrent elevations of the intraocular pressure (IOP) as secondary glaucoma. To investigate how HCMV affects the function of HTMCs, we analyzed the effects of HCMV infection on cultured HTMCs infected with the endothelial-adapted strain, TB40/E, of HCMV. We studied the induced molecular mechanisms focusing on the OAG-associated chemokines, IL-8 and CCL2. The HTMCs were analyzed for transcriptome changes using RNAseq analysis. Our results showed that HCMV infection activated interferon signaling and significantly increased the expression of IL-8 and CCL2. The IL-8-responsive transcriptional pathway was analyzed by using a CXCR2 antagonist which is associated with cellular movement and development of the hematological system. In contrast, the CCL2-sensitive pathway, assessed using a CCR2 antagonist, was linked to olfactory receptor signaling and keratinization. HCMV infection activated cell motility with the formation of lamellipodia and filopodia. The infection-induced activation of cell motility was dependent on both CXCR2 and CCR2, and IL-8 stimulated filopodia-mediated cell motility. HCMV infection also induced cell contraction that was dependent on CXCR2, but not on CCR2, and it involved the activation of Rac1/Cdc42. These results suggest that HCMV infection altered the cytoskeletal dynamics and contraction of the HTMCs in a CCR2- and CXCR2-dependent manner. These changes have the potential of causing an increase in the resistance to aqueous humor outflow in HCMV-associated anterior uveitis and corneal endotheliitis.